2015
DOI: 10.1589/rika.30.53
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Functional Prognosis of Proximal Femoral Fracture Patients

Abstract: This study examined the relation between functional prognosis, and nutritional status in patients with proximal femoral fracture. [Subjects and Methods] Two hundred and sixty-six patients with proximal femoral fracture were recruited for this study. Their mean age was 85.2 years. Logistic regression analysis was performed to determine the relationship between nutritional status and functional prognosis. [Results] Serum Albumin (Alb) ratios at admission were shown to significantly influence the recovery process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Since a cognitive impairment adversely affects the rehabilitation progress, it may result in poor functional recovery. Our results are congruent with what has been reported by Okamoto et al8 ) and Inoue et al 9. )…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Since a cognitive impairment adversely affects the rehabilitation progress, it may result in poor functional recovery. Our results are congruent with what has been reported by Okamoto et al8 ) and Inoue et al 9. )…”
Section: Discussionsupporting
confidence: 94%
“…In previous studies, serum albumin levels have been related to the nutritional status assessed by the Mini Nutritional Assessment Short-Form (MNA-SF)6, 7 ) , and serum albumin has been considered as an indicator of a person’s nutrition status6,7,8 ) . In a previous study, serum albumin ratios at admission were shown to significantly affect walking function recovery in the operative hip fracture patients8 ) . Malnourished patients were functionally more dependent and more likely to reside in an institutionalized setting.…”
Section: Discussionmentioning
confidence: 99%